Relationship between green entrepreneurship orientation, integration of opportunity and resource capacities and sustainable competitive advantage - Li, Wenjin; Sun, Yu; Gao, Yang (Frontiers in Psychology, 2022)
Green entrepreneurial orientation (GEO) and sustainability have been the hot topics in green entrepreneurship research. The GEO integrates market orientation (MO) and environmental orientation (EO), and enterprises need to increase resource investment. However, it is not clear whether this strategic orientation can help new ventures achieve sustainable competitive advantages (SCA). In addition, the integrated role of opportunities and resources in the process of green entrepreneurship cannot be ignored. To fill the gap, we analyzed survey data from 274 emerging green enterprises in China, and we examined the effect of GEO on SCA. Additionally, we proposed the concept of integration of opportunity and resources capabilities (IORC) by integrating the core factors of green entrepreneurship. It can be divided into internal integration (ITI) and external integration (ETI), and the moderating effect of IORC on this relationship was also inspected. The results indicated that GEO significantly affects SCA, and IORC positively moderates the relationships between GEO and SCA. Indeed, compared with the enterprises that adopt a single strategic orientation, enterprises that adopt GEO can obtain greater SCA. In addition, focusing on the internal and external integration of IORC can further enhance the acquisition of SCA. This study not only integrates the theories of entrepreneurship and sustainable development but also compensates for the lack of green entrepreneurship theory while providing practical guidance for new enterprises seeking to engage in green entrepreneurship.